2012
DOI: 10.1016/j.expneurol.2011.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on blood brain barrier and matrix metalloproteases following controlled cortical impact in mice

Abstract: Aging alters the ability of the brain to respond to injury. One of the major differences between the adult and aged brain is that comparable injuries lead to greater blood brain barrier disruption in the aged brain. The goals of these studies were to quantify the effects of age on BBB permeability using high field strength MRI T1 mapping and to determine whether activation of matrix metalloproteases, their inhibitors, or expression of blood brain barrier structural proteins, occludin, zonnula occludins-1 (ZO-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 73 publications
1
52
0
Order By: Relevance
“…Available evidence suggests that in AD and aging brains have leaky BBB manifested by increased endogenous IgG extravasation to the brain. 36,37 The exact causes for BBB dysfunction in AD are not well-known, however impaired clearance of A β from the brain across the BBB as well as A β ’s role in mediating increases in endothelial cell permeability, 25 have been proposed to enhance accumulation of cerebrovascular and parenchymal amyloid deposits. 38 Immunostaining results demonstrated that Crocus sativus extract significantly reduced IgG extravasation by 47% in 5XFAD mice brains (Figure 6A, P < 0.001), which was associated with increased expression of the tight junction protein cloudin-5 in brain microvessles by 38% (Figure 6B, P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Available evidence suggests that in AD and aging brains have leaky BBB manifested by increased endogenous IgG extravasation to the brain. 36,37 The exact causes for BBB dysfunction in AD are not well-known, however impaired clearance of A β from the brain across the BBB as well as A β ’s role in mediating increases in endothelial cell permeability, 25 have been proposed to enhance accumulation of cerebrovascular and parenchymal amyloid deposits. 38 Immunostaining results demonstrated that Crocus sativus extract significantly reduced IgG extravasation by 47% in 5XFAD mice brains (Figure 6A, P < 0.001), which was associated with increased expression of the tight junction protein cloudin-5 in brain microvessles by 38% (Figure 6B, P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Animal models of Fragile-x syndrome have indicated that minocycline, through inhibition of MMP-9, improves cognitive function and promotes maturation of dendritic spines in vivo and in vitro [28]. Recent work by Lee et al [29] has shown that MMP-9 levels are elevated in the brain of aged mice compared to adults. Though currently unknown, the age-related increase in MMP-9 may contribute to cognitive deficits that may be attenuated by minocycline treatment.…”
Section: Discussionmentioning
confidence: 99%
“…8 Regarding leukoaraiosis, blood-brain barrier disruption and vasogenic edema would be attributable to the pathogenesis of leukoaraiosis. 9 Age is the most important risk factor for leukoaraiosis.…”
Section: February 2014mentioning
confidence: 99%